Diferensiasi Gonad Ikan Nilem (Osteochilus vittatus) dengan Perlakuan Suhu: Diferensiasi Gonad Ikan Nilem - Aulidya Nurul Habibah; Rika P.C. Pertiwi; Titi Chasanah (BIOEDUSCIENCE, 2020)
Background: Gonad differentiation in some teleostei is a critical phase of gonad development. Gonad differentiation in some fish such as the tilapia group is influenced by environmental factors, namely temperature. The aim of this study was to determine the differentiation process of Nilem fish gonads (Osteochilus vittatus) under the influence of temperature. Methods: One day after fertilization (days postfertilization/dpf) fish were exposed to different medium temperature ranges, namely: 28-29 oC, 30-31 oC, 32-33 oC, and room temperature as a control for 35 days. The percentage of fish survival was calculated on the 35th day by calculating the number of surviving fish divided by the total number of fish in 1 tank times 100%. Thirty fish in each treatment were measured for body length at day 10 dpf and day 35 dpf to determine fish growth. Six fish 35 dpf from each treatment were fixed in 70% alcohol for making histological preparations using the paraffin method, Haematoxylin-Eosin staining. Fish survival data growth data in the form of fish length were analyzed using Anova. Gonadal differentiation data were analyzed descriptively. Results: There was no significant difference in the growth of fish in all treatment and control groups. The average survival rate of fish in all treatment and control groups was 100%. Observation of the gonads showed that the gonads were not differentiated in all treatment and control groups. Conclusion: The room temperature range up to 33 oC supports the growth of Nilem fish with gonad development in the indifferent gonad stage.